The subaltern theories of International Relations and the possible alternative worlds (2020)
The objective of this article is to visualize the possibility of alternative worlds to the current one from the analysis of the internal theoretical integrity of the subaltern theories of International Relations (Neogramscism, Critical Theory, Post-structuralism, Feminism and Post-colonialism). To fulfill this objective, a documentary investigation will be carried out. The methodology chosen for this purpose is a documentary analysis that aims to dissect the main arguments, key concepts and assessments made by emblematic exponents of subaltern theories. The main conclusion reached by this article is that despite common concerns about how to overcome the ideational structures of domination, subaltern theories face seemingly insurmountable obstacles that may jeopardize the possibility of subverting the established order. © 2020 Ariadna Ediciones. All rights reserved.